HYPERMASCULINITY IN THE CROODS FILM: A DESCRIPTIVE STUDY - Budianto, Lestari; Amaliyah, Salwa; Sugiarti, Dwi Wahyu (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
In the world of literary research, a film is a very interesting object of research. A film is a literary work that can provide a lot of values to human life. This study aims to explore the hypermasculinity that exists in the 3D animated film entitled The Croods. The film was released in 2013 and tells the story of a family led by a man named Grug. This study uses a descriptive qualitative method and the data from this research are formed from two types of data, namely the main data and supporting data. The main data of this study was obtained from the film "The Croods" while the supporting data are from websites. The data obtained are analyzed using four stages, namely data collection, data display, data reduction, and conclusion. The results of this study indicate that hypermasculinity is seen in the main character who is protective, caring, responsible, strong, brave, and stubborn. This finding is reflected in the dialogues, actions, and fashion that occur in the film.